Modeling Determinants of First-Day Returns from IPOs - Wessel,Ellinor; Millar,Scott; Winnberg,Carl (2005)
The primary purpose of this paper is to find the determinants of first-day returns on the Stockholm Stock Exchange. Our research will cover the 1996 – 2004 periods. Our secondary purpose is intended to find a profitable trading strategy with regard to future IPOs on the Stockholm Stock Exchange. By using regression analysis, focusing on company specific factors and the IPO process, we hope to find a function exhibiting statistical significance, determining future first-day returns from which construction of a profitable trading strategy will be possible. We have chosen a deductive attempt with a quantitative procedure through which we can draw general results. More specifically, we use multiple regression models to attain our purpose. IPO literature has generally done a good job in covering the theoretical perspective on why first-day returns exist. Within this area, Ritter is the foremost authority. The method of predicting first-day returns is derived from the assumption that first-day returns are explained as a function of company characteristics, stock market cycle and how the IPO is conducted. Our empirical foundation is built upon 258 firms, of which 124 where identified as clean IPOs. From this sample we were able to collect data, supplied by FI, in the form of company listing prospectuses, on 107 firms. Although our findings can be deemed successful, we have failed to find a model that determines first-day returns. This revelation is hardly surprising since doing so is virtually impossible. Instead, our findings show, with a high degree of certainty, which behavioural characteristics can be expected during the first-day of trading, given the input variables we have chosen. These results are what we base our trading strategy on.
Keywords: Initial Public Offerings; First day returns; Determinants; Regression analysis; Underpricing; Management of enterprises; Företagsledning, management